2021
DOI: 10.3389/fped.2021.754941
|View full text |Cite
|
Sign up to set email alerts
|

High Rate of Cytomegalovirus Detection in Cholestatic Preterm Infants

Abstract: Objectives: To evaluate the prevalence of cytomegalovirus (CMV) infection in preterm infants with cholestasis.Study design: Preterm infants (<37 weeks gestational age) with cholestasis were tested for CMV DNA using Taqman PCR in blood cells from sedimented whole blood, plasma, and urine. Infants were regarded as positive for CMV if any sample was tested positive. Their mothers were tested for CMV serostatus simultaneously. A control group of non-cholestatic preterm infants, and their mothers, were teste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 33 publications
0
1
0
Order By: Relevance
“…A few studies have reported on infectious diseases in the early stages of ICP offspring. Recently, a study reported that cytomegalovirus infection was considerably more frequent in preterm infants with cholestasis than in non-cholestatic offspring, and more necrotizing enterocolitis was prevalent among cytomegalovirus-positive cholestatic infants ( 30 ). Combined with our results, we postulate that ICP offspring may be more susceptible to inflammatory diseases.…”
Section: Discussionmentioning
confidence: 99%
“…A few studies have reported on infectious diseases in the early stages of ICP offspring. Recently, a study reported that cytomegalovirus infection was considerably more frequent in preterm infants with cholestasis than in non-cholestatic offspring, and more necrotizing enterocolitis was prevalent among cytomegalovirus-positive cholestatic infants ( 30 ). Combined with our results, we postulate that ICP offspring may be more susceptible to inflammatory diseases.…”
Section: Discussionmentioning
confidence: 99%